2008
DOI: 10.3200/jach.57.1.15-22
|View full text |Cite
|
Sign up to set email alerts
|

An Interactive Web-Based Method of Outreach to College Students at Risk for Suicide

Abstract: The method has considerable promise for encouraging previously untreated, at-risk college students to get help.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(116 citation statements)
references
References 16 publications
5
106
0
2
Order By: Relevance
“…A program tested at the University of California, San Diego School of Medicine found that of the 101 individuals who screened positive for significant depression or suicide risk, 48 accepted a referral to mental health treatment, with the majority of respondents attributing their entry into treatment to the screening (Moutier et al, 2012). Another university-based program used a webbased screening model that allowed individuals to connect anonymously with a clinician online (Haas et al, 2008). Those who were at moderate to high risk were also strongly encouraged to attend an in-person visit with a clinician.…”
Section: Screeningmentioning
confidence: 99%
“…A program tested at the University of California, San Diego School of Medicine found that of the 101 individuals who screened positive for significant depression or suicide risk, 48 accepted a referral to mental health treatment, with the majority of respondents attributing their entry into treatment to the screening (Moutier et al, 2012). Another university-based program used a webbased screening model that allowed individuals to connect anonymously with a clinician online (Haas et al, 2008). Those who were at moderate to high risk were also strongly encouraged to attend an in-person visit with a clinician.…”
Section: Screeningmentioning
confidence: 99%
“…There are reasons to believe that online counseling may be an acceptable approach in this digitally savvy generation, a recent study evaluated an interactive web-based program designed to screen students for depression and suicide risk. After the initial online screening, 24% of students entered into an online dialogue with a counselor, 19% later attended an in-person session with the counselor and 14% entered a treatment program [34]. SNSs may provide an innovative venue to provide access to online screening and follow-up resources.…”
Section: Future Research Approachesmentioning
confidence: 99%
“…Findings from the literature also provide early support for the use of the Internet for mental health promotion in youth in terms of assessment (Santor et al 2007), self-screening, (Donker et al 2009;Ercan et al 2006) mental health literacy (Burns et al 2009;Santor et al 2007;Larue et al 2009), prevention (Calear and Christensen 2010), intervention (Bruning Brown et al 2004;Crutzen and De Nooijer 2011;Fridrici and Lohaus 2009), and as a first point of entry into a mental health care system (Haas et al 2008). Moreover, due to 338 T. Halsall et al the sensitive nature of mental health issues and youth propensity for self-reliance (Rideout 2002;Marcus and Westra 2012), the Internet presents as a powerful resource for health promotion, especially around highly stigmatized health issues (Berger et al 2005;Naylor et al 2009).…”
Section: Introductionmentioning
confidence: 93%